Nutrition Education for Affordable, Nutritious and Tasty Meals (NEAT) in Early Childhood Education (ECE), Depok, West Java, Indonesia - Humayrah, Wardina; Astuti, Titin; Ulya, Salwa Nailil; Saputri, Andini (Journal of Community Empowerment for Health, 2025)
Introduction: During the pre-school period in Early Childhood Education (ECE), where children spend approximately 3-4 hours a day, there is a critical opportunity to instil balanced eating habits despite low knowledge and attitudes about nutrition in daily meals. The Nutrition Education for Affordable, Nutritious and Tasty Meals (NEAT) programme aims to improve the knowledge, attitudes and skills of teachers, parents, and students in providing nutritious, varied, tasty and economical healthy meals. Methods: This programme was held in Baitussalam ECE School, Depok, West Java, Indonesia, by involving the entire school community as participants, consisting of principals, teachers, students and parents. The socialisation and training of teachers and parents was carried out through Zoom Meetings with interactive discussion methods using electronic paperback media. In addition, the programme was carried out offline in two activities. Firstly, for parents with a healthy-economical meal education and competition and secondly for students with a game method using snake ladder mat and stickers. Results: The results showed that the nutritional knowledge and attitudes towards healthy and economical eating among teachers, parents and students improved after the programme. The challenge of this programme is to fit in with the schedules of the parents and to keep the students focused during the activities, but the enthusiasm of the participants was quite high. Conclusion: In conclusion, this programme improved nutritional knowledge and attitudes, despite scheduling challenges, and demonstrated high levels of participant enthusiasm and engagement.